A green modification technology of carbon nanotubes toward enhancing the tribological properties of aqueous-based lubricants. (February 2023) - Wang, Siyuan; Ren, Guanlin; Li, Wenqi; Wang, Bin; Wei, Fuhua; Liang, Zhao; Chen, Ding
Abstract: Herein, a green and efficient method is proposed for preparing highly stable aqueous dispersions to realize the potential applications of carbon nanotubes in water. Functionalized carbon nanotubes (CNTs@CMC-Na) were rapidly prepared using a microwave-assisted ball milling apparatus. Sodium carboxymethyl cellulose was grafted on carbon nanotubes through various actions and CNTs@CMC-Na exhibited excellent dispersibility, which increased the thermal conductivity of pure water by 97.6 %. The tribological tests and surface analysis indicate that CNTs@CMC-Na have protective, mending, and cooling effects at the friction interface. The CNTs@CMC-Na aqueous dispersion (0.2 wt%) reduced the average friction coefficient, average wear width, and temperature of the friction interface by 50.13 %, 58.3 %, and 38.9 %, respectively. This study provides a new idea for the preparation of lubricant additives. Graphical Abstract: A green and efficient chemical approach to preparing aqueous-based lubricant additives was proposed. Functionalized carbon nanotubes (CNTs@CMC-Na) were rapidly and successfully prepared using a microwave-assisted ball milling apparatus. CNTs@CMC-Na aqueous dispersion can be used directly as lubricants, which exhibit stable dispersion, high thermal conductivity, and excellent tribological properties. ga1 Highlights: CNTs@CMC-Na were prepared rapidly using microwave-assisted ball milling apparatus. The hydrophilicity and dispersibility of CNTs@CMC-Na in water were excellent. CNTs@CMC-Na can significantly improve the tribological properties of pure water. The dispersion and lubrication mechanisms of CNTs@CMC-Na in water were discussed.